Brunatna edukacja. Kultura, nauka i wychowanie w Trzeciej Rzeszy - Drozdowicz, Jarema (Humaniora. Fundacja dla humanistyki, 2016)
The system of education in the Third Reich represented a specific way of combining ideological indoctrination with a certain set of national myths. It was based on a racial discourse and anti-Semitism, as well it persuaded an imperative of total domination over non-German groups of people. This paper deals with the distinctive features of the mentioned educational system in order to deliver a better understanding of functioning of education within a totalitarian regime. Education is her not just simply a selected area of authoritarian politics but an important tool in the mechanism of maintaining control over people’s minds through changing their worldview.
Keywords: nazi education; Third Reich; World War II; science; volk; ideology